The adverse events of CDK4/6 inhibitors for HR+/ HER2- breast cancer: an umbrella review of meta-analyses of randomized controlled trials - Dongqing Pu; Yue Wu; Debo Xu; Guangxi Shi; Hanhan Chen; Dandan Feng; Mengdi Zhang; Jingwei Li (Frontiers Media S.A., 2024)
Background: The clinical selection of three CDK4/6 inhibitors presents a challenging issue, owing to the absence of distinct clinical case characteristics, biomarkers, and their comparable clinical benefits in progression-free survival and overall survival To inform clinical treatment decisions, we conducted a comprehensive evaluation of the adverse events associated with CDK4/6 inhibitors in combination with endocrine therapy for hazard ratio+/HER2-breast cancer.Methods: We searched Cochrane, PubMed, Embase, and Web of Science databases from their inception until 1 August 2022. The results were summarized narratively, and we assessed the methodological quality, reporting quality, and evidence quality of AEs by AMSTAR-2, PRISMA, and GRADE.Results: Our analysis included 24 meta-analyses systematic reviews that evaluated the quality of AEs in 13 cases of early breast cancer (EBC) and 158 cases of advanced breast cancer The addition of CDK4/6 inhibitors was found to significantly increase AEs of any grade and AEs of grade 3 or higher in early breast cancer, along with a significant increase in the risk of treatment discontinuation. In advanced breast cancer, high and moderate-quality evidence indicated that CDK4/6 inhibitors significantly increased AEs across all grades, including grade 3/4 AEs, leucopenia, grade 3/4 leucopenia, neutropenia, grade 3/4 neutropenia, anemia, grade 3/4 anemia, nausea, grade 3/4 constipation, fatigue, pyrexia, venous thromboembolism abdominal pain, and cough. However, they did not significantly elevate the incidence of grade 3/4 diarrhea. Subgroup analysis revealed that palbociclib primarily increased hematologic toxicity, particularly grade 3/4 neutropenia, anemia, and thrombocytopenia. Ribociclib was mainly associated with grade 3/4 neutropenia, prolonged QT interval, and alopecia. Abemaciclib was closely linked with diarrhea and elevated blood creatinine levels.Conclusion: The AEs associated with CDK4/6 inhibitors vary, necessitating individualized and precise clinical selection for optimal management. This approach should be based on the patient's medical history and the distinct characteristics of different CDK4/6 inhibitors to improve the patient's quality of life.Systematic Review Registration: [https://systematicreview.gov/], identifier [CRD42022350167]